2016
DOI: 10.1111/os.12256
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Safety of Intravenous Tranexamic Acid in Simultaneous Bilateral Total Knee Arthroplasty: A Systematic Review and Meta‐analysis

Abstract: The objective of this systematic review and meta-analysis was to evaluate the efficacy and safety of i.v. tranexamic acid (TXA) in simultaneous bilateral total knee arthroplasty (TKA). Potentially relevant published reports were identified from the following electronic databases: Medline, PubMed, Embase, ScienceDirect and Cochrane Library. RevMan v5.3was used to pool data. Two randomized controlled trials and four case-control studies met the inclusion criteria. The current meta-analysis identified significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…As an analogue of the amino acid lysine, tranexamic acid (TXA) can competitively inhibit plasminogen activation and plasmin binding to fibrin to achieve the effect of anti-fibrinolysis, [ 14 ] and thus reduce perioperative blood loss and transfusion rate. [ 9 , 15 ] There are 3 common methods of TXA administration in THA and TKA patients: intravenous, [ 16 ] topical, [ 17 ] and combined application. [ 6 ] Many studies have shown that combined application is the most effective regimen.…”
Section: Introductionmentioning
confidence: 99%
“…As an analogue of the amino acid lysine, tranexamic acid (TXA) can competitively inhibit plasminogen activation and plasmin binding to fibrin to achieve the effect of anti-fibrinolysis, [ 14 ] and thus reduce perioperative blood loss and transfusion rate. [ 9 , 15 ] There are 3 common methods of TXA administration in THA and TKA patients: intravenous, [ 16 ] topical, [ 17 ] and combined application. [ 6 ] Many studies have shown that combined application is the most effective regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Tranexamic acid (TXA) effectively decreases perioperative blood loss via intravenous [8], oral [9], and topical [10] routes and appears to be safe [11], [12]. One of the earliest randomized studies demonstrating the efficacy of TXA in reducing blood loss after total joint arthroplasty was published in 1997 [13], and it has since been adopted in many medical and surgical specialties [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that one‐third of patients who received THA required transfusion of one to three units of blood, and the reported range of transfusion rates are between 25% and 84%. The risks of blood transfusion include immunological reactions, volume overload, infection, intravascular hemolysis, renal failure, and even death. Therefore, determining how to reduce bleeding and, therefore, transfusions following THA has become an important and urgent problem to be resolved for orthopedist.…”
Section: Introductionmentioning
confidence: 99%